Pembatasan Upaya Hukum Kasasi dalam Perkara Perdata sebagai Upaya Meningkatkan Efektivitas Peradilan di Indonesia - Akhmad; Elhady, Aminullah; Kasman, Kasman (TSAQAFAH, 2025)
This article examines scholarly views on the precision (á¸abá¹) of the Prophet's Companions in narrating hadiths by comparing early and contemporary hadith literature. The aim of this research is to reveal whether the quality of precision is truly guaranteed in the Prophet's Companions as is their integrity ('adÄlah), and to explain various arguments related to this matter. This research also attempts to address criticisms questioning the validity of Companions' narrations on the grounds that they are not ma'á¹£Å«m (infallible); as ordinary humans with the potential for error and forgetfulness, and not all Companions having the same level of intelligence (á¸abá¹). This research is library-based with a qualitative method that conducts in-depth analysis of authoritative works in hadith literature, covering phases from early to contemporary. The research finds that Imam al-á¸¤Äfiáº“ Ibn á¸¤ajar al-'AsqalÄnÄ« is among the scholars who explicitly state that all Companions possess the quality of á¸abá¹, placing the status of Companions at the highest position in the levels of al-ta'dÄ«l (authentication). Meanwhile, the opinion initiated by Imam al-á¹¢an'ÄnÄ« and followed by several contemporary scholars states that the guarantee of Companions' integrity does not automatically guarantee their precision, with various arguments including the fact that some Companions had erred and forgotten when conveying hadiths. However, after conducting in-depth research on the texts of both opinions, the researcher concludes that the difference between the two groups of scholars is verbal in nature. The first group does not deny the possibility of forgetfulness and errors among the Companions, while the second group does not explicitly determine which individual Companions are considered to lack the quality of á¸abá¹. Both groups agree that errors that occurred among the Companions can still be tolerated and do not damage their overall precision.